2019
DOI: 10.1002/tqem.21633
|View full text |Cite
|
Sign up to set email alerts
|

Urban air pollution from the open burning of municipal solid waste

Abstract: This study estimates the contribution from the open burning of municipal wastes in some of Nigeria's major cities to atmospheric levels of air pollutants. Information obtained on open burning emission factors and municipal solid waste (MSW) generation estimates was combined to estimate annual levels of the pollutants from the open burning of MSW. Per capita distributions of pollutants were calculated on the basis of cities’ populations. The estimates of inorganic emissions across the cities studied were from 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Some studies carried out to assess the effect of open burning of municipal solid wastes on air quality have shown that the types of air pollutants and the levels of pollution are dependent on the composition of the solid wastes burnt. In a survey carried out by [33] in Korea to evaluate the emission levels of harmful substances from test combustion of individual types of domestic municipal solid waste, it was estimated that the average annual emissions of hazardous materials from frequent open burning were 71 tons for PM10, 46.6 tons for PM2.5, 914 kg for heavy metals, and 67 kg for PAHs with open burning creating nearly 0.44% of regional air pollution from PM10.Similarly, [34] estimated annual levels of the pollutants from the open burning of MSW in Nigerian cities and found that wide varieties of both inorganic and organic air pollutants were released with associated human health and environmental impacts. [35] carried out an investigation to assess the amount of air pollution emitted from household solid waste open burning in Thailand and discovered that a total of 4.09 Mt/year of wastes were burnt in open areas.…”
Section: Results Of Air Quality Measurementsmentioning
confidence: 99%
“…Some studies carried out to assess the effect of open burning of municipal solid wastes on air quality have shown that the types of air pollutants and the levels of pollution are dependent on the composition of the solid wastes burnt. In a survey carried out by [33] in Korea to evaluate the emission levels of harmful substances from test combustion of individual types of domestic municipal solid waste, it was estimated that the average annual emissions of hazardous materials from frequent open burning were 71 tons for PM10, 46.6 tons for PM2.5, 914 kg for heavy metals, and 67 kg for PAHs with open burning creating nearly 0.44% of regional air pollution from PM10.Similarly, [34] estimated annual levels of the pollutants from the open burning of MSW in Nigerian cities and found that wide varieties of both inorganic and organic air pollutants were released with associated human health and environmental impacts. [35] carried out an investigation to assess the amount of air pollution emitted from household solid waste open burning in Thailand and discovered that a total of 4.09 Mt/year of wastes were burnt in open areas.…”
Section: Results Of Air Quality Measurementsmentioning
confidence: 99%
“…Polycyclic (polynuclear) aromatic hydrocarbons (PAHs) constitute a group of over 100 chemical species but only about 16 of them are listed as priority PAHs by the United States Environmental Protection Agency and are so frequently monitored. The 16 priority PAHs have been reported to be toxic and carcinogenic ( Cousin and Cachot, 2014 ; Das et al., 2014 ; Abdel-Shafy and Mansour, 2016 ; Okedere et al., 2019 ).…”
Section: Common Anthropogenic Air Pollutants: Sources and Adverse Effmentioning
confidence: 99%
“…There are hardly budgetary provisions for integrated solid wastes management hence bulk of these wastes end in open dumpsites and subsequently burnt; hence, contributing to anthropogenic loadings of air pollutants. Municipal wastes are usually composed of wide varieties of substances; hence, emission of wide varieties of pollutants with adverse human health effects ( Okedere et al., 2019 ). To address this, an efficient waste management system which is currently missing in almost all the federating States of Nigeria has to be evolved.…”
Section: Drivers Of Anthropogenic Air Pollutants In Nigeriamentioning
confidence: 99%
See 1 more Smart Citation
“…Odour pollution is relatively under-researched compared with other forms of pollution but can affect the quality of life and restrict outdoor activity. In the context of Nigeria, open burning (as opposed to recycling) plastic/waste is widely accepted (Okedere et al 2019;Anyanwu & Adefila 2014;Abdulwakeel & Bartholdson, 2018) and is reportedly common in other African countries and parts of China (Madigele et al 2017;Otsyina et al 2018). Controlled waste burning by incinerators can be a necessity to deal with hazardous waste, such as medical waste however open, uncontrolled, residential burning of waste can create significant public health and environmental hazards (Cogut, 2016).…”
Section: Atmospheric Miasmas and Harm To Human Healthmentioning
confidence: 99%